2021
DOI: 10.20338/bjmb.v15i2.208
|View full text |Cite
|
Sign up to set email alerts
|

The impact of motor competence on energy expenditure during object control skill performance in children and young adults

Abstract: BACKGROUND: An understanding of how motor skill performance levels relate to energy expenditure (EE) is an important, yet relatively unexplored topic that may better inform physical activity interventions. AIM: This study examined the impact of motor competence (MC) on EE during the performance of object control skills in children and young adults. METHOD: Forty-two children (Mage 8.1 years) and 40 young adults (Mage = 23.4 years) completed sessions of throwing and kicking at varying intensity intervals. Polyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Most physical activities that children engage in, require competence in a variety of movement skills (i.e., physical education, structured games, sports). Thus, higher levels of skill facilitate successful and continued participation in multiple types of activities over time and would impact physical activity and CRF both directly and indirectly (5,11,48). The differences in MC levels across profiles suggest that, indeed, skill levels were developed prior to age 11 in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most physical activities that children engage in, require competence in a variety of movement skills (i.e., physical education, structured games, sports). Thus, higher levels of skill facilitate successful and continued participation in multiple types of activities over time and would impact physical activity and CRF both directly and indirectly (5,11,48). The differences in MC levels across profiles suggest that, indeed, skill levels were developed prior to age 11 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to understand that the physical activity environment impacts not only the learning of MC skills, but also the amount and intensity (e.g., light, moderate, vigorous) of physical activity, which impacts CRF (5). Thus, although all physical activities are beneficial, exploring and learning a wide variety of movement skills and being able to transfer those skills to higher-level movement applications provides a diversified foundation for both directly (via greater neuromuscular demand) (11) and indirectly (via sustained activities associated with practice, gameplay, and performance) enhancing CRF (12). Better CRF allows children to continue physical activities for longer periods of time and thus provides more opportunities for motor development and physical activity accumulation (5,7).…”
mentioning
confidence: 99%
“…The consistent associations found between FMS and PA indicate that a high level of motor competence can contribute to long-term PA engagement [ 67 ]. Minimal research, however, exists pertaining to the intensity of activity accrued during the performance of FMS activities [ 68 ] or the associated quality of skill execution.…”
Section: Components Of Fitt Principlementioning
confidence: 99%
“…Recent studies with populations of children and adolescents have examined energy expenditure during the performance of object-control skills (kick, throw, strike) [ 68 , 69 ]. The Sacko et al (2019) study ( n = 42; 22 males; mean age = 8.1 ± 0.8 years) reported that the practice of kicking, throwing, and striking at a rate of two maximal-effort attempts per minute appears to meet the threshold for moderate-intensity PA as it surpasses the 4.0 metabolic equivalent (METs) [ 69 ].…”
Section: Components Of Fitt Principlementioning
confidence: 99%
See 1 more Smart Citation